1 Corinthians - Reasoner,Mark, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2025)
This commentary offers you a deep dive into the first century city of Roman Corinth, insight from patristic commentaries on 1 Corinthians, and a focus on Paul's call for unity in the church. Its thesis is that Paul counters the Corinthians' prioritization of knowledge by calling them to focus on the message of the crucified and risen Christ while embodying the virtue of love to animate and unify the church. From beginning to end, this commentary evokes appreciation of Paul's letter of 1 Corinthians as an artifact of first century social history and prompts reflection on the letter's challenge to Christ-followers for what it means to be the church.